Pengaruh Kinerja Dinas Perhubungan dalam Peningkatan Retribusi Terminal Kota Medan - Simorangkir, Enda Noviyanti; Purba, Oktavianus Frans William Parasian (Lembaga Yasin AlSys, 2023)
The Department of Transportation is a type of organization that focuses on maximizing productivity so that the desired results can be achieved. The method used in this study is the scribent method, which utilizes quantitative data with a high need for organizing, analyzing, and evaluating all available facts using a technique called time series analysis of product. The North Sumatra Transportation Service revealed that from the following three indicators all of them were quite successful in highlighting new investment data, especially when comparing the capitalization of new investments with future new investments. To increase economic growth. The municipal government of Medanm continues to improve terminal development techniques, especially maintenance of terminal facilities. Many issues have arisen in the process of increasing the speed of tax collection during terminal deployment by the North Sumatra Transportation Agency, and many tasks have been approved by the organization.